Variability of fatty acid profiles, oxidative stability and nutritive quality of oil in selected soybean genotypes - Matoša Kočar, Maja; Vila, Sonja; Petrović, Sonja, inženjerka agronomije; Rebekić, Andrijana; Sudarić, Aleksandra; Duvnjak, Tomislav; Markulj Kulundžić, Antonela (2020)
The purpose of this study (2010‒12) was to investigate the fatty acid profiles (palmitic – PA, stearic – SA, oleic – OA, linoleic – LA, linolenic – LNA, saturated fatty acids – SFA, monounsaturated fatty acids – MUFA, polyunsaturated fatty acids – PUFA), oxidative stability (MUFA/PUFA, OA/LA), and nutritive quality (LA/LNA) of oil produced by 13 early soybean genotypes created at the Agricultural Institute Osijek, Croatia. The analysis of variance determined significant effect of genotype (G), year (Y), and GxY interaction on all examined traits. The correlation analysis indicated the most important positive correlation existed between the SA and OA, SA and LNA, and LA and LNA, and the most important negative relationship between OA and LA, and OA and LNA. The principal component analysis yielded four significant principal components (PCs) with the eigenvalues >1, which together accounted for 57.84% of the total variability in the data set. The Eigen analysis of the correlation matrix loadings indicated MUFA/PUFA, MUFA, OA/LA, and OA mostly contribute to the PC1 axis and are in a positive correlation with it, while PUFA, LA, and LNA mostly contribute to a negative direction. These results will facilitate the planning of future breeding programs, aimed at adjusting the fatty acid profiles according to the needs of the processing industry and end consumers.
Cilj ovoga istraživanja (2010. – 2012.) bio je procijeniti sadržaj masnih kiselina (palmitinska – PA, stearinska – SA, oleinska – OA, linolna – LA, linolenska – LNA, zasićene masne kiseline – SFA, mononezasićene masne kiseline – MUFA, polinezasićene masne kiseline – PUFA), oksidacijsku stabilnost (MUFA/PUFA, OA/LA) i nutritivnu kakvoću (LA/LNA) ulja 13 ranih genotipova soje nastalih u Poljoprivrednome institutu Osijek, Hrvatska. Analizom varijance utvrđeno je postojanje varijabilnosti za sva testirana svojstva, pri čemu su genotip (G), godina (Y) i GxY značajni izvori varijacije. Najznačajnije pozitivne korelacije su utvrđene između SA i OA, SA i LNA i LA i LNA, a najznačajnije negativne između OA i LA i OA i LNA. Analizom glavnih sastavnica utvrđeno je kako postoje četiri primarne osi sa svojstvenim vrijednostima >1, koje zajedno objašnjavaju 57,84% varijabilnosti ukupnih podataka. Prva primarna os (PC1) najviše je u pozitivnome smjeru vezana za svojstva MUFA/PUFA, MUFA, OA/OALA i OA, a u negativnome smjeru za PUFA, LA i LNA. Ovi rezultati bit će od pomoći pri planiranju budućih oplemenjivačkih programa usmjerenih k prilagodbi sastava i sadržaja masnih kiselina prema potrebama prerađivačke industrije i krajnjih korisnika.
Bibliografija: 38 jed.
Summary ; Sažetak.
Keywords: Soja -- Masne kiseline -- Nutritivna kakvoća -- Oksidacijska stabilnost